2016
DOI: 10.1590/1983-40632016v4638011
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of rice plants sprayed with herbicides

Abstract: Understanding the physiological defense behavior of plants subjected to herbicide application may help to identify products with higher or lower capacity to cause oxidative stress in crops. This study aimed at evaluating the effect of herbicides in the antioxidant activity of rice plants. The experimental design was completely randomized, with six replications. Treatments consisted of the herbicides bentazon (photosystem II inhibitor; 960 g ha-1), penoxsulam (acetolactate synthase inhibitor; 60 g ha-1), cyhalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…[18] showed that penoxsulam induced DNA damage to the Procambarus clarkii. Penoxsulam also induced oxidative stress in Oryza sativa [19] and Oreochromis niloticus [20]. Penoxsulam exposure in the A. cepa might result in generation of ROS which could decrease root growth and MI and also increase CAs and DNA damage.…”
Section: Resultsmentioning
confidence: 99%
“…[18] showed that penoxsulam induced DNA damage to the Procambarus clarkii. Penoxsulam also induced oxidative stress in Oryza sativa [19] and Oreochromis niloticus [20]. Penoxsulam exposure in the A. cepa might result in generation of ROS which could decrease root growth and MI and also increase CAs and DNA damage.…”
Section: Resultsmentioning
confidence: 99%
“…At 24 hours after bentazon application (Nohatto et al 2016) and 96 hours after glyphosate application (Moldes et al 2008) vegetal material was collected for quantification of the activity of oxidative stress enzymes, dismutase (SOD), catalase (CAT) and peroxidase (POX). Approximately 1 g of vegetal material (fully expanded leaves from the upper third of the plant) was collected and packed in aluminum foil envelopes, quickly frozen with liquid nitrogen, and stored at -20°C until the time of analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The application of doses of 0.11, 0.022, 03.03 and 0.044 micrograms of herbicides reduced 13, 24, 35 and 46 percent activity of polyphenol oxidase activity of wheat, respectively (Figure 9). In a test, the effect of Bentazone (photosynthesis inhibitor in photocisteemic 2), Penoxsulam (acetylacetate synthesis inhibitor) and Haloxyfopbutyl (acetyl coenzyme carboxylase inhibitor inhibitor) on rice plant, it was determined that the use of bentazone and pinocylamreduced catalase activity, increased H 2 O 2 levels and increased lipid oxidation (Nohatto et al, 2016). In a trial on the effect of Bentazone and Penoxsulam herbicides on rice plant, the use of herbicides reduced the activity of catalase activity, based on which researchers have suggested these herbicides as inhibiting the enzyme activity (Abedi and Pakniyat, 2010).…”
Section: Activity Of Antioxidant Enzymesmentioning
confidence: 99%